Enhancing Students’ Critical Thinking and Sustainability Awareness through the Concept Attainment Model–Education for Sustainable Development (CAM-ESD): A Quasi-Experimental Study in Indonesian Upper Secondary Biology - Berti Yolida; Median Agus Priadi; Rini Rita T. Marpaung; Ismah Fatimah; Dian Ratna Sari; Laila Puspita; Kadek Dewi S (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2026)
Critical thinking skills and sustainability awareness are essential competencies for addressing global challenges in the 21st century. However, students in Indonesia still demonstrate relatively low levels of both competencies. This study examines the effect of the Concept Attainment Model (CAM) based on Education for Sustainable Development (ESD) on the improvement of students’ critical thinking skills and sustainability awareness in ecosystem learning. A quasi-experimental design with a non-equivalent control group was employed, involving two tenth-grade classes at one public high school in East Lampung, Indonesia (experimental group, n = 28; control group, n = 29). Data were collected through pretests, posttests, and sustainability awareness questionnaires. Data were analyzed using normalized gain (N-gain), independent samples t-test, and effect size (Cohen’s d). Results showed that the experimental class achieved higher improvement in critical thinking skills than the control class, with moderate N-gain values (0.47 vs 0.37) and a large effect size (d = 1.12. Sustainability awareness improved more substantially in the experimental group than in the control group, with emotional awareness achieving a high N-gain (0.89 vs 0.52), behavioral and attitude awareness showing moderate improvement (0.61 vs 0.27), and sustainability practice awareness demonstrating lower but still higher gains in the experimental class (0.51 vs 0.31. These results indicate that the integration of CAM with ESD effectively enhances both cognitive and affective domains of learning. The study highlights the potential of this approach for fostering competencies that are critical to sustainable education and suggests its application across various subjects and educational levels.